2016
DOI: 10.1021/acsami.6b02814
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Responsivity of Organic–Metal Oxynitride Hybrid Heterointerface Phototransistor

Abstract: Amorphous metal oxides are attractive materials for various sensor applications, because of high electrical performance and easy processing. However, low absorption coefficient, slow photoresponse, and persistent photoconductivity of amorphous metal oxide films from the origin of deep-level defects are obstacles to their use as photonic applications. Here, we demonstrate ultrahigh photoresponsivity of organic-inorganic hybrid phototransistors featuring bulk heterojunction polymers and low-bandgap zinc oxynitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…The photocurrent increases with the increasing V G at fixed V SD ( V SD  = 30 V), and increases with the increasing V SD at fixed V G ( V G  = 9 V), which show the modulation of gate voltage and source-drain voltage on electronic signal. The gate voltage is considered to provide an efficient route for the charge dissociation in the OPT devices 38 . Higher drain voltage effectively draws electrons to weaken the recombination of photogenerated carriers 14,38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocurrent increases with the increasing V G at fixed V SD ( V SD  = 30 V), and increases with the increasing V SD at fixed V G ( V G  = 9 V), which show the modulation of gate voltage and source-drain voltage on electronic signal. The gate voltage is considered to provide an efficient route for the charge dissociation in the OPT devices 38 . Higher drain voltage effectively draws electrons to weaken the recombination of photogenerated carriers 14,38 .…”
Section: Resultsmentioning
confidence: 99%
“…The gate voltage is considered to provide an efficient route for the charge dissociation in the OPT devices 38 . Higher drain voltage effectively draws electrons to weaken the recombination of photogenerated carriers 14,38 . The reproducible photoswitch function in signal amplification and photodetection provides the OPTs potential applications in cost-effective flexible organic optoelectronics.
Figure 4Dynamic photoresponse behavior of the PTCDI-C 13 H 27 thin-film phototransistor.
…”
Section: Resultsmentioning
confidence: 99%
“…[139,142,166,167] Xu et al demonstrated a poly(N-alkyl diketopyrrolo-pyrrole dithienylthieno[3,2-b]thiophene) (DPP-DTT): [6,6]-phenyl-C61-butyric acid methylester (PCBM)-based phototransistor working at the NIR region, [138] in which the BHJ effectively trapped one type of charge and allowed the opposite charge transport to provide a high photocurrent gain. [48] A broader sensing range of up to 940 nm and a higher linear dynamic range of ≈122 dB is achieved by applying an in situ grown thin ZnO hole-blocking layer. Therefore, the photogenerated holes could circulate in the channel many times before being recombined with trapped electrons located in isolated PCBM domains.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The application of organic phototransistors is promising for high‐performance NIR sensing. Various materials and devices have been reported for optical sensing covering the NIR region, and further device modifications based on phototransistors have made particularly for NIR sensing to boost the sensitivity . For organic thermoelectric devices, the role of OFETs is not for practical applications, but a powerful tool for fundamental study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation